The Influence of Work Life Balance, Work Environment and Compensation Towards Millennial and Gen Z Employee Performance : The Influence of Work Life Balance, Work Environment and Compensation Towards Millennial and Gen Z Employee Performance - Murtadha Khairi Zhafran Yusuf; Defi Insani Saibil (Jurnal Ilmu Perbankan dan Keuangan Syariah, 2026)
This study aims to examine the influence of work-life balance, work environment, and compensation on employee performance in Islamic banks in the Special Region of Yogyakarta. This study uses a comparative quantitative approach and purposive sampling technique on employees classified as millennials and Generation Z. Data was collected from 100 respondents who met the criteria. Data collection methods include literature review and questionnaire surveys. Data analysis was conducted using SPSS 26. The results of this study indicate that work-life balance does not significantly influence millennial employees, while the other two variables have a significant influence. For Generation Z employees, compensation does not significantly influence them, while the other two variables have a significant influence. The results of the simultaneous test indicate that all independent variables have a significant effect on the dependent variable for both generations. The results of the Independent T-Test comparison indicate no significant difference in the effect of all independent variables on employee performance between the two generations. This study is expected to be beneficial for the Islamic banking industry, particularly in understanding the differences in characteristics between millennial and Generation Z employees to maximize their performance